OPTIMAL CONDITIONS FOR OXIDIZING PHENOL IN WATER BY FENTON AND PHOTO-FENTON PROCESSES - Blas López, H. A. (2017)
Phenol can be degraded to almost 100 % within a few minutes via Fenton and photo-Fenton processes. Its degradation and the ratio of initial molar concentrations of oxidant and catalyst increase in inverse senses, and a ratio of 38.4 was optimal for aqueous solutions contaminated with 20 ppm of phenol. In addition to this, the use of ultraviolet-A light enhanced degradation when compared to shorter wavelengths.